(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the development of linguistic, speech competencies of students on the basis of modern approaches to improving the content of native language education, the content and essence of these approaches, and the feedback of Methodist scientists on the cultivation of modern approaches to scientific, logical thinking, lexical, morphological, speech units and reading, reading, communication culture through Uzbek literary language norms were analyzed.